GEOTECHNICAL INVESTIGATION OF THE ROCK SLOPE STABILITY PROBLEMS OCCURRED AT THE FOUNDATIONS OF THE COASTAL BYZANTINE WALL OF KAVALA CITY, GREECE - Loupasakis, C.; Spanou, N.; Kanaris, D.; Exioglou, D.; Georgakopoulos, A. (Bulletin of the Geological Society of Greece, 2010)
The coastal Byzantine wall of Kavala is located at the Panagia peninsula and it is founded on the Simvolou granite. The granite rock mass appears to be fractured by joint sets with very high persistence (>20m) and very wide spacing (60cm – 2m), forming large rock blocks. Further more, the Panagia peninsula is intersected by numerous parallel normal faults, forming extended zones of intensively fractured rock mass. Along the coastline the granite appear to be eroded by the sea waves, forming small gulfs around the faults. The Byzantine wall is founded along the edge of the fractured slopes forming the coast line of the peninsula, arising issues about the safety of the historical construction. The joint sets form numerous rock wedges with unfavourable orientation, many sections of the slopes are undercut by the wave erosion and in the majority of the fault zones the rock mass presents intensive fragmentation. The above described condition of the rock mass was recorded in detail along the entire coast line and all unstable sections were located. A full set of support measures was proposed for all unfavourable sections aiming to the improvement of the geotechnical behaviour of the rock mass, constituting the foundation formation of the Byzantine wall.